(untitled) (GESTIÓN Y TENDENCIAS, 2017)
Technological innovation is commonly associated with the generation of new and radical products, in which R&D and appropriability strategies predominate. Incremental innovations, by contrast, arise from established designs and lack the power to create new markets. Against this backdrop, imitation emerges as a complex and controversial phenomenon. It is normally associated with acquiring competitive advantages easily and opportunistically. This article addresses the phenomenon of imitation in the technology industry and discusses the role of novelty, intellectual property, and their implications in emerging economies.